On the design of high-speed energy-efficient successive-approximation logic for asynchronous SAR ADCs *Project supported by the National Natural Science Foundation of China (Nos. 61204033, 61331015), the Fundamental Research Funds for the Central Universities (No. WK2100230015), and the Funds of Science and Technology on Analog Integrated Circuit Laboratory (No. 9140C090111150C09041). (August 2017) - Yang, Jiaqi; Li, Ting; Yu, Mingyuan; Zhang, Shuangshuang; Lin, Fujiang; He, Lin
Abstract: This paper analyzes the power consumption and delay mechanisms of the successive-approximation (SA) logic of a typical asynchronous SAR ADC, and provides strategies to reduce both of them. Following these strategies, a unique direct-pass SA logic is proposed based on a full-swing once-triggered DFF and a self-locking tri-state gate. The unnecessary internal switching power of a typical TSPC DFF, which is commonly used in the SA logic, is avoided. The delay of the ready detector as well as the sequencer is removed from the critical path. A prototype SAR ADC based on the proposed SA logic is fabricated in 130 nm CMOS. It achieves a peak SNDR of 56.3 dB at 1.2 V supply and 65 MS/s sampling rate, and has a total power consumption of 555 μ W, while the digital part consumes only 203 μ W.